Development of KoMaCu Learning Media for Probability: An Innovative Digital Comic to Enhance Learning Effectiveness - Sihombing, Floricytha; Putri, Amelia; Utami, Devina Zuhra; Sherlyta, Sherlyta; Suwanto, Fevi Rahmawati (Insitut Agama Islam Negeri Kerinci, 2025)
This study aimed to develop and evaluate the validity, practicality, and effectiveness of KoMaCu (Funny Mathematics Comics) as a digital comic-based learning medium for probability topics among ninth-grade students at Imelda Private Junior High School, Medan. The study was motivated by students’ low motivation and achievement in mathematics due to predominantly conventional and monotonous instructional practices. KoMaCu was designed by integrating visual narratives with the Realistic Mathematics Education (RME) approach to promote contextual and meaningful learning. The study employed a Research and Development (R&D) methodology using the ADDIE model, encompassing analysis, design, development, implementation, and evaluation stages. Data were collected through expert validation sheets, student response questionnaires, and pre-test and post-test assessments. The participants consisted of 18 ninth-grade students. The validation results indicated that KoMaCu achieved a highly valid category in terms of content, language, and media design. Practicality testing yielded a feasibility score of 66%, indicating positive student responses. Furthermore, students’ learning outcomes improved substantially, with the mean score increasing from 13.3 in the pre-test to 40.5 in the post-test. These findings demonstrate that KoMaCu is valid, practical, and effective in enhancing students’ understanding and motivation in learning probability, thereby contributing to the development of innovative digital learning media in mathematics education.